PENGARUH PENGALAMAN, PENDIDIKAN, CURAHAN WAKTU DAN MENTAL KEWIRAUSAHAAN TERHADAP KEBERHASILAN INDUSTRI KECIL KRUPUK DI DUSUN POJOK DESA BULUSARI KEDIRI - Djunaedi Djunaedi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The aim of this research is to examine whether experience, education, time expense, and entrepreneur mentality have influence to achievement. The data was gathered through the administration of questionnaire as well as direct interview with a selected subjects in Bulusari village at Kediri City. By using F test, T test, multiple linier regression in analyzing data, this study found, first, experience, education, time expense, and entrepreneur mentality have influence to achievement. Second, dominant factor is entrepreneur mentality.